Experience, Seniority and Gut Feeling—A Qualitative Examination of How Swedish Police Officers Perceive They Value, Evaluate and Manage Knowledge When Making Decisions - Eliasson, Michelle (Frontiers in Education, 2021)
There is a debate in current scholarship regarding whether or not education and training is an effective tool to change police officers’ conduct. Compared to the United States, Sweden has longer training for officers who experience 2 years of academic training and 6 months of practical training. The Swedish police training is also, contrary to the American training, standardized. This paper aims to investigate how Swedish officers value, evaluate and manage knowledge when making decisions. To examine this further 27 qualitative interviews were conducted with 14 male and 13 female Swedish police officers during 2018. The interviews were analyzed using inductive thematic analysis in both English and Swedish to uncover themes and codes. Findings suggest that police officers utilize experience, seniority, and gut feeling when valuing, evaluating and managing knowledge. Furthermore, the results imply that certain types of knowledge are valued differently by officers. These findings can inform how and if education can be used as a tool to potentially change how officers in the US and other countries make their decisions.